Content Analysis of The Quality of Engineering Education (QEE) in The Indonesian Junior High School Science Curriculum - Zahidsyahtya, Muhammad Amiq; Nur'aini, Anugrah Putri; Sulaeman, Nurul Fitriyah; Nuryadin, Atin; Efwinda, Shelly (Paedagoria : Jurnal Kajian, Penelitian dan Pengembangan Kependidikan, 2026)
In Indonesia, the engineering component in STEM education is critical yet remains poorly understood. This study aims to assess the representation of engineering education using the Quality of Engineering Education (QEE) framework within the Science Curriculum Phase D. The method employed is content analysis using a descriptive quantitative and qualitative approach within the QEE framework developed by Moore (2014). The study reveals that 10 out of 12 QEE elements are identifiable within the curriculum, with the Engineering Tools (Etool) element being the most dominant. However, two elements remain absent: the Process of Design (POD) and Concepts of Engineering and Engineers (CEE). These findings indicate that the quality of Engineering Education at Phase D in Indonesia remains limited. The results suggest that the Indonesian Science Curriculum for Junior High Schools still needs further development so that STEM components are explicitly represented and can serve as a firm reference for teachers to begin implementing STEM-based learning.